Bilateral vestibulopathy with positive Tullio phenomenon. (31st May 2017) - Finn, Sigrid; Dietzek, Maren; Karvouniari, Panagiota; Klingner, Carsten M.; Neumann, Rotraud; Guntinas‐Lichius, Orlando; Witte, Otto W.; Axer, Hubertus
Abstract : We describe the case of a 34‐year‐old patient presenting with the unique combination of bilateral vestibulopathy in combination with noise‐ and pressure‐induced nystagmus. Bilateral vestibular dysfunction was demonstrated by pathological results in video‐based head impulse testing as well as in caloric testing. In contrast, cervical vestibular‐evoked myogenic potentials were normal, demonstrating normal sacculus function. Due to the positive Tullio phenomenon, semicircular dehiscence syndrome was excluded. Recently, this symptom combination was related to the histopathological finding of vestibular atelectasis. Level of Evidence: NA. Laryngoscope, 128:1223–1225, 2018